1991
DOI: 10.1002/gcc.2870030107
|View full text |Cite
|
Sign up to set email alerts
|

Consistent cytogenetic aberrations in hepatoblastoma: A common pathway of genetic alterations in embryonal liver and skeletal muscle malignancies?

Abstract: Cytogenetic analyses of four consecutive hepatoblastomas revealed near-diploid stemline karyotypes with relatively simple chromosome aberrations. Cytogenetic abnormalities shared by each tumor included trisomy for all of part of chromosome 2 and trisomy for chromosome 20. In two cases, partial trisomy for chromosome 2 resulted from direct duplication of long arm material with the shortest region of overlap being 2q23-2q35. In one tumor, each metaphase also contained a variable number of double minute chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…Similar 1q imbalances have also been described, often as secondary changes, in other pediatric neoplastic disorders, such as acute lymphoblastic leukemia, retinoblastoma, Wilms tumor, and Ewing sarcoma, indicating that these aberrations are related to tumor progression [30,31]. Because of the frequent involvement of 1q12 and 1q21 in HBT [19,22,24,28] (also, the present investigation], FISH analyses were performed to try to map the breakpoints more precisely. Among the four cases analyzed, two were informative as regards 1q abnormalities, and both were found to display pericentromeric breakpoints.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar 1q imbalances have also been described, often as secondary changes, in other pediatric neoplastic disorders, such as acute lymphoblastic leukemia, retinoblastoma, Wilms tumor, and Ewing sarcoma, indicating that these aberrations are related to tumor progression [30,31]. Because of the frequent involvement of 1q12 and 1q21 in HBT [19,22,24,28] (also, the present investigation], FISH analyses were performed to try to map the breakpoints more precisely. Among the four cases analyzed, two were informative as regards 1q abnormalities, and both were found to display pericentromeric breakpoints.…”
Section: Discussionsupporting
confidence: 65%
“…Several previous cytogenetic studies have shown frequent structural as well as numerical abnormalities of chromosome 8 in HBT, often resulting in gain of 8q and loss of 8p [5,19,[21][22][23][24][25][26][27][28][29], but, again, these changes are not specific for HBT. On the contrary, similar chromosome 8 aberrations have been reported in a wide variety of neoplastic disorders [14], suggesting that these imbalances are of general importance in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of patients with hepatoblastoma do not have either syndrome. To our knowledge, cytogenetic analysis has been reported in only 21 confirmed hepatoblastomas in the pediatric age group (Petkovic et al, 1985;Mascarello et al, 1990;Bardi et al, 1991Bardi et al, , 1992Fletcher et al, 1991;Soukup et al, 1991;Anneren et al, 1992;Tonk et al, 1994;Swarts et al, 1996;Schneider et al, 1997). These studies have demonstrated that the most common recurring abnormalities are trisomies for chromosomes 2 and 20, and a recurrent translocation involving chromosomes 1 and 4 has been identified in a minority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37] Trisomy of chromosomes 2 and 8 and aberrations at the long arm of chromosome 1 (around 1q21) have also been shown in several cases of hepatoblastomas. [38][39][40][41] However, these karyotypic findings shed scarce light on the putative oncogenes or tumor suppressor genes involved in hepatoblastoma development and progression.…”
Section: Discussionmentioning
confidence: 99%